A cluster-based QoS multicast routing protocol for scalable MANETs - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (Korea Society of Internet Information, 2011)
Recently, multicast routing protocols become increasingly important aspect in Mobile Ad hoc Networks (MANETs), as they effectively manage group communications. Meanwhile, multimedia and real-time applications are becoming essential need for users of MANET. Thus it is necessary to design efficient and effective Quality of Service (QoS) multicast routing strategies. In this paper, we address the scalability problem of multicast routing protocols to support QoS over MANETs. In particular, we introduce a Position-Based QoS Multicast Routing Protocol (PBQMRP). Basically, the protocol based on dividing the network area into virtual hexagonal cells. Then, the location information is exploited to perform efficient and scalable route discovery. In comparison with other existing QoS multicast routing protocols, PBQMRP incurs less control packets by eliminating network flooding behavior. Through simulation, the efficiency and scalability of PBQMRP are evaluated and compared with the well-known On-Demand Multicast Routing Protocol (ODMRP). Simulation results justify that our protocol has better performance, less control overhead and higher scalability.